Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Smart Jungle Adventure Terhadap Pemahaman Konsep Siswa Kelas V - Devi, Revanda Tirzanita; Hawa, Anni Malihatul (Universitas PGRI Semarang, 2025)
This study aims to examine the influence of the discovery learning model assisted by the Smart Jungle Adventure media on students' conceptual understanding. The issue addressed is the low level of students' conceptual understanding in the learning process. This research employs a quantitative approach with the population consisting of all fifth-grade students at SDN Susukan 01, and the sample includes students from classes VA and VB of SDN Susukan 01. Data analysis was conducted using normality tests, homogeneity tests, independent sample t-tests, and regression tests. The results of the study indicate: (1) There is a significant difference between the experimental class, which utilized the discovery learning model assisted by Smart Jungle Adventure media, and the control class, which used the discovery learning model without the media. This is evidenced by a significance value of 0.000 0.05 based on the independent t-test. (2) The discovery learning model assisted by Smart Jungle Adventure media significantly influences students' conceptual understanding, as shown by a significance value of 0.000 0.05 based on the regression test. The conclusion of this study is that the discovery learning model assisted by Smart Jungle Adventure media is effective in improving students' conceptual understanding.